A sustained reduction in the rate of severe intraventricular hemorrhage in very low birth weight infants: a novel quality improvement project in a large perinatal-neonatal centre in Asia - Ibrahim, Thowfique; Agarwal, Arpan; Abdul Haium, Abdul Alim; Visruthan, Nirmal Kavalloor; Badillo, Maria Chona; Dela Puerta, Rowena; Banas, Janlie Lizaso; Sarjono, Sharifa; Noorul Amin Alawdeen, Fareed Muhammed Bin; Sultana, Rehana; Rajadurai, Victor Samuel (Frontiers in Pediatrics, 2025)
ObjectiveSevere IVH (SIVH) stands out as a leading cause of poor neuro-developmental outcomes, including cognitive, attention and motor impairment in very low birth weight (≤1.5 kg, VLBW) infants. The study aims to reduce the rate of severe intraventricular hemorrhage (SIVH) by 50% in very low birth weight (VLBW) infants admitted to the level III C neonatal intensive care unit (NICU) in Singapore.MethodIn this quality improvement (QI) study, VLBW infants admitted to NICU from 2011 to 2021 (n = 2215) were categorized into four periods: (a) pre-intervention 2011to 2012, (b) Intervention (2013 to 2017), (c) post-intervention (2018 to 2019), and (d) sustainment (2020 to 2021) periods, respectively. A multidisciplinary team identified key drivers for SIVH. A set of care bundles involving eight protocolized interventions was applied. Infants with SIVH were analyzed with an RC-PC-S process (Root Cause- Process Compliance - System), which includes a structured template by a Quality Assurance (QA) committee; recommendations were implemented in the unit to modify practices. Data were collected prospectively, and univariate and multivariate logistic regression analyses were conducted.ResultsOf 2,215 Infants who met the study criteria, Ninety infants were excluded. Detailed data were collected from 2,125 infants (390, 1,000, 370, and 365 in the baseline, intervention, post-intervention, and sustainment periods, respectively). The mean gestational age was 28·6 and 28.8 in the intervention and post-intervention periods, respectively, and were comparable across the 4 study periods. The rate of SIVH was 5.9% in the pre-intervention period and 4.4% and 1.9% (adjusted OR 0.266, p = 0.006, 44/1,000 vs. 7/370) in the intervention and the post-intervention periods, respectively, representing a reduction of 57%. The rate of SIVH in the sustainment period was 2·7%. The reduced SIVH was associated with reduced mortality, adherence to process measures, and no change in balancing measures.ConclusionA multipronged modified QI approach implementing an evidence-based SIVH prevention bundle and RC-PC-S analysis was associated with a sustained significant reduction in the rate of SIVH in VLBW infants. RC-PC-S is a potential QI tool for reducing severe IVH and other key neonatal morbidities in VLBW infants.